The transformative role of artificial Intelligence in the event management industry / Abdul Hamid Abdul Halim, Norol Hamiza Zamzuri and Ayu Rohaidah Ghazali - Abdul Halim, Abdul Hamid; Zamzuri, Norol Hamiza; Ghazali, Ayu Rohaidah (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2023)
This opinion paper explores the burgeoning influence of Artificial Intelligence (AI) within the event management industry. AI has emerged as a powerful tool, offering innovative solutions for event planning, execution, and attendee engagement. This paper provides a comprehensive overview of AI's role in event management, discussing its applications, benefits, and potential drawbacks based on contemporary researches and publications. By analysing six (6) current trends and four (4) critical reception of AI in the event industry, we aim to shed light on its transformative potential and its implications for the future of event management. At the end of the paper, the researchers provide recommendations on how to navigate the obstacles in implementing AI technology in event management. This paper is critical in its role to ignite discussions regarding AI implementation in event industry as there are currently very few academic writings on this topic.